FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT WANITA USIA SUBUR MEMILIH METODE KONTRASEPSI MOW (METODE KONTRASEPSI WANITA) DI DESA BUTUH - setyo, dhini hariyo; -, saryono; Iswati, Ning (LPPM STIKES MUHAMMADIYAH GOMBONG, 2011)
Increasing the number of residents is a major issue for countries in the world, especially developing countries like Indonesia. One effort that needs to be done by the government to handle this problem is to encourage and reactivate the Indonesian national program of family planning for. A secure contraception is more effective contraceptive than other contraceptives, but users are still very particular in Butuh Village, Purworejo District. The objective of this research is to find out the factors affecting fertile women interest in choosing tubectomy contraception methods in the Butuh Village Purworejo District.This study was an analytical research with cross sectional approach. The data were collected by using questionnaires. There were 31 respondents taken as theÂ samples by using purposive sampling. This research show that by using Â chi square correlation statistics there are a correlation between the number of children factor (p = 0.010), economic factor (p = 0.002), and socio-cultural factors (p = 0.035) with the interest of fertile women and there is no correlation between knowledge factor (p = 0.778) with fertile women interests in choosing tubectomy contraceptive methods. There are correlation between the number of children, economic, social and cultural with and there is no correlation between knowledge factors with fertile women interests in choosing tubectomy contraceptive methods. Keywords: Family planning, MOW, fertile woman